Standardizing Wudhu Place Design for Standing Position User Using Quality Function Deployment (QFD) - Oktaviandri, Muchamad; Mukrim Bin Azman, Muhammad; Pradhana Revi, Dipo; Zaki Zaidan, Hilman; Syas, Mulyanti (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2025)
The wudhu place is where Muslims perform ablution, washing particular parts of the body using water before performing prayer (shalat). Previous study has focused on finding the best wudhu place design for sitting positions. However, there are not many studies focusing on standardizing the wudhu place for standing position. Therefore, this paper attempts to address the gap in the research by studying the ergonomic aspect and standardizes for designing male wudhu places for standing positions using Quality Function Deployment (QFD). This includes the voice of the customer and the House of Quality. QFD is an effective design method to integrate ergonomics needs and comfort into wudhu place design, as it explicitly addresses the translation of customer requirements into engineering characteristics. This method is employed to identify the important criteria for improving the design of the wudhu place. Data is collected from existing and customer surveys of wudhu place. The objective of this study is to compare and to find the best measure for standardizing the wudhu places to enhance comfort and ergonomics. Based on the study, three main criteria have been standardized: a) the distance between the tap water from the standing position should be 74 cm to 84 cm b) the distance between two taps should be 14 cm to 17 cm c) the distance of the tap water from the wall should be 64 cm to 71 cm.